2007
DOI: 10.1103/physrevc.76.051603
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear symmetry energy and neutron skins derived from pygmy dipole resonances

Abstract: By exploiting Coulomb dissociation of high-energy radioactive beams of the neutron-rich nuclei [129][130][131][132]134 Sb, their dipole-strength distributions have been measured. A sizable fraction of "pygmy" dipole strength, energetically located below the giant dipole resonance, is observed in all of these nuclei. A comparison with available pygmy resonance data in stable nuclei ( 208 Pb and N = 82 isotones) indicates a trend of strength increasing with the proton-to-neutron asymmetry. On theoretical ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
274
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(292 citation statements)
references
References 34 publications
(43 reference statements)
15
274
0
3
Order By: Relevance
“…In addition to the identification of the prominent Giant Dipole Resonance (GDR), the electric dipole response of neutron-rich nuclei displays a smaller concentration of strength at lower energies, that is commonly referred to as the Pygmy Dipole Strength (PDS) [5]. Data on the PDS have been used in the past to constrain the symmetry energy and to obtain * xavier.roca.maza@mi.infn.it information on the neutron skin thickness of neutronrich nuclei [6][7][8][9][10][11]. In one of the earliest applications of uncertainty quantification to the domain of energy density functionals (EDFs), Reinhard and Nazarewicz carried out a covariance analysis to correlate the neutron skin thickness of 208 Pb to the properties of both finite nuclei and infinite nuclear matter [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the identification of the prominent Giant Dipole Resonance (GDR), the electric dipole response of neutron-rich nuclei displays a smaller concentration of strength at lower energies, that is commonly referred to as the Pygmy Dipole Strength (PDS) [5]. Data on the PDS have been used in the past to constrain the symmetry energy and to obtain * xavier.roca.maza@mi.infn.it information on the neutron skin thickness of neutronrich nuclei [6][7][8][9][10][11]. In one of the earliest applications of uncertainty quantification to the domain of energy density functionals (EDFs), Reinhard and Nazarewicz carried out a covariance analysis to correlate the neutron skin thickness of 208 Pb to the properties of both finite nuclei and infinite nuclear matter [1].…”
Section: Introductionmentioning
confidence: 99%
“…So far the E1 response in medium-heavy to heavy nuclei has been studied via Coulomb excitation in inverse kinematics in the region of 130,132 Sn [4,21] and in 68 Ni [22]. Both experiments were sensitive to excitation energies above the corresponding particle thresholds.…”
Section: The Strength Of the Pdrmentioning
confidence: 99%
“…In addition it has gained interest in the last decade due to its possible connections to the neutron skin of atomic nuclei and properties of nuclear matter [3][4][5][6][7] as well as reaction rates in the synthesis of heavy elements [8][9][10]. However, the microscopic structure of the PDR, its collectivity and the robustness of the connections to other properties mentioned above are a matter of ongoing discussions.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that this low energy strength increases with the N/Z ratio. The problem of how the E1strength evolves for nuclei far from stability in the neutron rich side is presently one of the interesting topics in nuclear structure since it provides information on the neutron skin and on the nuclear equation of state for asymmetric nuclear matter, relevant for the study of neutron stars [29,30]. In addition, the strength of the PDR is presently attracting a lot of attention as the dipole strength distribution affects reaction rates in astrophysical scenarios where photodisintegration reactions are important, i.e., in hot stars and stellar explosions [31].…”
Section: Moving Towards Neutron or Proton Rich Nucleimentioning
confidence: 99%